A new method for the toughness assessment of mobile crane components based on damage mechanics. (16th May 2022) - Li, Dongsong; Könemann, Markus; Dölz, Michael; Münstermann, Sebastian
Abstract: The characterization of toughness properties in standard Charpy or fracture mechanics tests calls for thickness requirements to be met. Therefore, the characterization of toughness properties is a problem for thin‐walled structures. Replacing Charpy impact toughness testing by impact notch tensile testing can solve this problem. However, the toughness requirements are still expressed in terms of standard test results. Therefore, a framework is proposed here for translating these standard test requirements into impact notch tensile test requirements. The proposed framework relies on numerical simulations with a phenomenological damage mechanics model, which uses state‐of‐stress‐dependent, strain‐based criteria for the prediction of local damage and global fracture. This model takes the effects of non‐proportional strain paths into account and applies different criteria for cleavage and ductile fracture in order to predict correctly the activation of cleavage and ductile fracture mechanisms in the corresponding numerical simulations.